2021
DOI: 10.1007/s00214-021-02821-1
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between organic molecules and a gold nanoparticle: a quantum chemical topological analysis

Abstract: The ligands at the surface of a gold nanoparticle (GNP) have a significant influence on the optical and physical properties, that may render different functionalities to the GNP. Therefore, there is a need in understanding the nature of the interaction at atomic resolution in order to allow rational design of GNPs with desired physico-chemical properties. The interaction between Au 79 and a series of small organic molecules has been systematically studied at the quantum mechanical level : methane, methanol, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…For the low-density configuration, the aromatic ring lies parallel to the metallic surface. This result is in accordance with Tandiana et al , 47 who indicated that benzene preferred to adopt a flat configuration on gold nanoparticles. In contrast, when the density is high, the steric hindrance would induce a strongly different orientation of benzene so that the molecule is now oriented vertically to the surface.…”
Section: Resultssupporting
confidence: 92%
“…For the low-density configuration, the aromatic ring lies parallel to the metallic surface. This result is in accordance with Tandiana et al , 47 who indicated that benzene preferred to adopt a flat configuration on gold nanoparticles. In contrast, when the density is high, the steric hindrance would induce a strongly different orientation of benzene so that the molecule is now oriented vertically to the surface.…”
Section: Resultssupporting
confidence: 92%
“…Before irradiation (t = 0) the maxima of the suspensions were found at 534 nm and 540 nm (figures 5(b) and (d)) revealing more intense variations in plasmon frequency relative to the AuNP-ABMA suspensions. These interactions must be associated with adsorption of DCPIP on the NP surface (Tandiana et al 2021). During the first 20 min of irradiation at 532 nm there was a hypsochromic shift of 18 nm from the maximum of the suspension while its intensity decreased > 35% (figures 5(a) and (b)).…”
Section: Laser Irradiation Of Abma and Dcpip In The Presence Of Aunpmentioning
confidence: 96%
“…However, in contrast to the irradiation of isolated AuNPf dissolved in toluene (figure 1(c)) in the presence of ABMA and DMSO the λ max showed a slight red shift (4 nm) in the first 10 min of irradiation (figure 6(e)) suggesting the occurrence of changes in the plasmon properties due to: (a) probable aggregation of AuNPf; (b) interactions between ABMA and DMSO, already described (section 3.2.1.). The high electrophilicity of Au NPs alters their surface electron density in the presence of organic molecules affecting λ max (Kamat et al 2002, Tandiana et al 2021. As the irradiation time increased the λ max shifted to blue while observing a remarkable total intensity variation (>60%) and band broadening (figures 6(c) and (e)).…”
Section: Laser Irradiation Of Abma and Dcpip In The Presence Of Aunpfmentioning
confidence: 99%
“…Our previous work on the interaction with a series of small organic molecules has indicated that benzene prefers to adopt a flat configuration (with the aromatic plane interacting parallel to the surface of GNP). 31 This could be attributed to the optimized interaction between the HOMO of benzene and LUMO of GNP, as well as the maximization of dispersion interactions. However, previous studies of aromatic containing compounds deposited on metal surfaces have indicated that the aromatic plane is not always adsorbed in a parallel configuration.…”
Section: Introductionmentioning
confidence: 99%